2017
DOI: 10.1080/21622965.2017.1392861
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic competence of children with autism spectrum disorder. Impact of theory of mind, verbal working memory, ADHD symptoms, and structural language

Abstract: The primary aim of this study is to increase the existing knowledge about the pragmatic skills of children with autism spectrum disorders (ASD). Specifically, the study has two objectives. The first is to provide a profile of characteristics based on The Children's Communication Checklist (CCC-2) pragmatics scales (inappropriate initiation, stereotyped language, use of context, nonverbal communication, and general pragmatics) and narrative task indicators. To this end, children with ASD will be compared to chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 56 publications
7
19
0
4
Order By: Relevance
“…This group also showed significantly less mastery of daily living skills and poorer adaptive skills than the "Higher ToM abilities" profile, which showed less widespread impairment. Our results corroborate previous findings that have linked the prevalence of ToM in ASD to the degree of autistic symptoms (Lerner et al, 2011;Hoogenhout and Malcolm-Smith, 2017) or to pragmatic and social competence (Tager-Flusberg, 2001;Mazza et al, 2017;Baixauli et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…This group also showed significantly less mastery of daily living skills and poorer adaptive skills than the "Higher ToM abilities" profile, which showed less widespread impairment. Our results corroborate previous findings that have linked the prevalence of ToM in ASD to the degree of autistic symptoms (Lerner et al, 2011;Hoogenhout and Malcolm-Smith, 2017) or to pragmatic and social competence (Tager-Flusberg, 2001;Mazza et al, 2017;Baixauli et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Kuijper et al (2017) reported a mean (SD) Structural Language Score in the ASD group of 20.4 (9.0), and a mean (SD) General Pragmatic Score of 37.4 (13.1), both of which are higher (indicating larger deficits) compared with the present sample. In a more recent study, Baixauli-Fortea et al (2019) report a mean (SD) Structural Language Score in the ASD group of 19.0 (9.4), which is close to the observed value in the present sample. There are, however, important differences between these two and the present study; smaller sample sizes (n = 36 and n = 52), the inclusion of only participants with normal range cognitive abilities, as well as a more limited age range under study (6-12 and 7-11 years), which may limit comparability.…”
Section: Discussionsupporting
confidence: 90%
“…The overall extent and profile of structural language deficits did not differ between children with and without an ASD diagnosis, and is consistent with the language profile reported from previous studies in school-aged children with ASD, as reviewed by Boucher (2012). Further, the observed extent of deficits is comparable to previous studies in school-aged children with ASD (Helland et al 2012;Kuijper et al 2017;Baixauli-Fortea et al 2019). Clinicians and researchers have long been aware of the high comorbidity between ASD and other NDDs (Lord et al 2018), as well as their potential impact on specific aspects of language and communication.…”
Section: Structural and Pragmatic Language Deficits Across The Range Of Autistic Symptomssupporting
confidence: 89%
“…A medium to large correlation has been found in TD children (Matthews et al, 2018 ; Wilson & Bishop, 2021 ). There is also a growing evidence supporting that structural language deficits were common and associated with reduced pragmatic competence in children with LI and ASD (Baixauli-Fortea et al, 2019 ; Greenslade et al, 2019 ; Levinson et al, 2020 ; Reindal et al, 2021 ). Subsequent studies should focus on the interactions between the two domains and compare how the reciprocal relationships are manifested in children with or without neurodevelopmental disorders.…”
Section: Future Directionsmentioning
confidence: 99%